Indian Ocean strategies through the ages : with rare and antique maps - Bhargava, M. L. (New Delhi : Reliance Publication, 1990)
with a foreword by Prof. Satish Chandra
Keywords: Indian Ocean -- Maps; Indian Ocean -- Strategic aspects